Validation of the Submetric Accuracy of Vertical Positioning of PSs in C-Band - Perissin, D. (IEEE geoscience and remote sensing letters, 2008)
The permanent scatterers (PSs) technique is an operational tool in the context of spaceborne synthetic aperture radar interferometry for monitoring the displacement of radar targets with millimetric accuracy. Recently, the target localization capability of the PS technique has been subject of study, and the possibility of generating digital elevation models (DEMs) and digital terrain models (DTMs) by means of the height of a sparse set of points has been evaluated. In this letter, for the first time, the PS height estimate has been validated by exploiting about 250,000 spot heights at street level derived from photogrammetric techniques in the urban area around Milan, Italy. The very high correlation between the two independent measurements confirms the theoretical submetric accuracy of vertical positioning. A multitrack PS DTM has then been generated and compared to the spot heights together with the corresponding Shuttle Radar Topography Mission (SRTM) DEM, showing the very high improvement given by the PS technique to the freely available topographic data. The results have been obtained by processing about 300 European Space Agency (ESA) European Remote Sensing (ERS) satellite and Envisat images acquired from two descending tracks and an ascending one over Milan.